Edukasi Pengetahuan Gizi Olahraga bagi Atlet Siswa SSB Pandawa Footbal Academy Sukoharjo - Ellyas, Intan Suraya; Kristiyanto, Agus; Mariyanto, Muhammad; Lelono, Sarjoko; Riyadi, Slamet; Utomo, Tri Aprilijanto; Daryanto, Daryanto; Wulansari, Dasih Ayu (Jurnal Pengabdian Olahraga Masyarakat, 2024)
The Pandawa Football Academy (PFA) in Sukoharjo is one of the top football schools (SSB) in the Sukoharjo and Solo Raya regions. The academy has achieved various accomplishments at the district, provincial, and national levels. However, based on observations and interviews, it was found that during the training and learning process, comprehensive nutrition knowledge had not been provided to the student athletes. Knowledge about nutritious food ingredients, meal selection, and meal planning during training and competition periods was only obtained from classroom material, which was not in-depth. There has not been any specific training for student athletes on the benefits of sports nutrition knowledge that can support performance during competitions. Therefore, this community service activity aims to increase the sports nutrition knowledge of student athletes using a service-learning method, which includes an educational stage for the student athletes. The results of this training showed an increase in the sports nutrition knowledge of the student athletes at PFA Sukoharjo (p-value 0.0000.01). There was an increase in the level of sports nutrition knowledge from an average category of moderate to high, using the NUKYA questionnaire in the Indonesian language version. The participants in this training were categorized as adolescent athletes. The nutrition knowledge gained can serve as a foundation for these student athletes as they become professional players.